PRACTICALIZATION OF INFORMATION TECHNOLOGY-BASED ENTREPRENEURSHIP LEARNING MODELS IN SUPPORTING THE MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) PROGRAM IN HIGHER EDUCATION - MARKANI; HAMSU ABDUL GANI; ANDI MUHAMMAD IDKHAN (Pascasarjana Universitas Negeri Makassar, 2023)
This study aims to determine the level of practicality of the information technology-based entrepreneurship learning model in supporting the independent campus learning program. This research uses the process of 4D model development stages with an experiential learning based blended learning approach by adapting the 4D development model which consists of several stages including: (1). Define, (2). Design, (3). Development, dan (4). Dessiminate. The assessment of the practicality of media experts on the use of media obtained an average score of 84.07% with a very practical category and the implementation of the learning model obtained an average score of 85.20% with a very practical category. The implementation of the learning model by students gave a positive response with an average of 81.45% and a lecturer response with an average of 82.80%. Based on expert agreement, student and lecturer responses, the learning model of information technology-based entrepreneurship courses is declared feasible and practical to implement.